An exploratory study on the perceptions of Zimbabwean women activists regarding the Domestic Violence Act (2007) - Lipeleke, Freddy (2014)
Includes bibliographical references.The overall aim of the study was to explore the perceptions of Zimbabwe women activists regarding the Domestic Violence Act (2007) in that country. The study surveyed fourteen women activists in Zimbabwe to determine their perceptions on the strengths and weaknesses of the Act, the challenges of implementing the Act, and lastly, their recommendations with regard to the amendments, if any, that they would want to see made to the Act. The respondents comprised women who worked for organisations that advocated and lobbied for the rights of women in Zimbabwe. The research design was qualitative, and a purposive sampling technique was employed to recruit the respondents. In-depth face-to-face interviews were used to gather data for the study. Most of the respondents who were interviewed were lawyers, although there were also a significant number of social workers and a teacher. The study established that the Act had both strengths and weaknesses. The most significant strengths of the Act was the criminalisation of domestic violence in Zimbabwe. This therefore meant that the problem of domestic violence was now receiving much needed attention from the state and its law enforcement agents. Another strength of the Act was the fact that the definition of domestic violence was expanded to include other cultural practices that violate the rights of women. These included such practices as forced virginity tests and forced marriages, as well as the pledging of the girl child as a form of payment, practices which hitherto were not classified as criminal offences